Peningakatan Kemampuan Numerasi Awal Anak Usia 5-6 Tahun Melalui Media Turtle Sorting Color - Juliatul Paidah, Egia; Nugraha, Dadan; Syafri, Herman (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
The problem addressed in this study stems from the low early numeracy skills of children aged 5–6 years at TK Perwari 1, Tasikmalaya City. Initial observations revealed that the children struggled to understand basic number concepts, simple arithmetic operations, and object classification based on quantity and color. Learning activities focused primarily on lecture-based methods and the use of worksheets (LKA), which proved less effective in stimulating children’s cognitive development, particularly in early numeracy. This research aims to improve children’s early numeracy skills through the use of the Turtle Sorting Color media a concrete learning tool made from plywood decorated with turtle images, where each turtle’s shell is crafted from used plastic bottles serving as containers for colorful pom-poms. Each turtle is labeled with a number to guide children in grouping pom-poms by color and quantity. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, implemented over two cycles. The research subjects consisted of 15 children from group B at TK Perwari 1. Data collection techniques included observation, documentation, and field notes, analyzed through descriptive qualitative and quantitative methods. Findings revealed a significant improvement in children's early numeracy skills. The average achievement increased from 36.25% in the pre-cycle, to 64.59% in the first cycle, and reached 88.33% in the second cycle. Children became more active, focused, and capable of understanding early numeracy concepts in a concrete and enjoyable manner. This study concludes that the Turtle Sorting Color media is effective as a learning aid to enhance early numeracy skills in children aged 5–6 years. The media offers an innovative alternative aligned with play-based learning approaches in early childhood education